Paxlovid plus glucocorticoids treatment in severe Omicron infected patients with hypoxaemia: A prospective multiple-center cohort study - Yu-Ji Wang; Nan Su; Jun-Hong Jiang; Guo-Peng Xu; Ran Wang; Da-Xiong Zeng; Jiao Zhu (PLoS ONE, 2025)
Background Administration of Paxlovid in early stage has been proved to reduce the risk of hospitalization or death by 89% in mild to moderate COVID-19 patients with high-risk. There were few evidences of Paxlovid in severe COVID-19 patients. RECOVERY study has previously shown that the use of glucocorticoids reduces the risk of death in hospitalized COVID-19 patients requiring oxygen or ventilatory support. The efficacy of Paxlovid plus glucocorticoids in COVID-19 patients with hypoxaemia is unclear. Methods In this multiple-centers prospective study, we collected the data of hospitalized adult Omicron infected subjects with hypoxaemia at 4 hospitals, who were treated with glucocorticoids or Paxlovid plus glucocorticoid. We compared the efficacy of Paxlovid plus glucocorticoids (P + GCS group) vs. glucocorticoids (GCS group). A 28-day composite outcome of disease progression was evaluated. Results Totally 266 Omicron infected patients with hypoxaemia were enrolled in this study. There was no difference in most of the baseline characteristics in two groups, including ages, sex and underlying diseases. The 28-day composite outcome in severe patients of P + GCS group was significantly lower than that of GCS group (16.9% vs. 33.8%, P = 0.013). The viral shedding time was shorter in P + GCS group than that in G group (6 days vs. 8 days, P = 0.015). The hospitalized time in severe patients of P + GCS group was significantly shorter than that of GCS group (15 days vs. 17 days, P = 0.0008). Cox analysis showed the benefit of P + GCS in sub-group of MODS, CRP ≥ 36 mg/L, d-dimer ≥1 µg/L, creatinine ≥ 90µmol/L). Conclusions Our study demonstrated the benefit of Paxlovid plus glucocorticoid administration in hospitalized Omicron infection patients with hypoxaemia. These results, as least partly, supported direct evidence about the necessity of antiviral treatment in severe COVID-19 patients with hypoxaemia.